An empirical study on the influence of sustainable environmental manufacturing practice on firm performance - Adebambo, Hameed O.; Ashari, Hasbullah; Nordin, Norani (Penerbit UMT, 2015)
Environmental problem has been linked to the operational activities of manufacturing firms as they yield production with economic values under the guidance of environmental regulation.Hence, sustainable environmental practice is one of the critical factors in the competition and performance among manufacturers. This study investigates the influence of sustainable environmental manufacturing practices (SEMP) on firm performance.A survey questionnaire was used to collect data from 103 manufacturing companies in Malaysia and it was analysed with SmartPLS.The result found a significant relationship between SEMP and environmental performance, but could not find an evidence of a significant relationship between SEMP, and financial and operational performance.This implies that SEMP is yet to be considered as a strategic resource in achieving competitive advantage and better firm performance among manufacturing companies.Therefore, the study suggests that the environmental policy maker should create more awareness to enlighten the manufacturing practitioners not only to perceive sustainable environmental practices as ethical but also as a strategic factor in achieving better firm performance.